Comparative growth performance and carcass characteristics of guinea fowl (Numida meleagris) and three chicken genotypes - Zelleke, G.; Urge, Mengistu; Animut, G.; Esatu, Wondmeneh; Dessie, Tadelle (African Journals Online, 2022)
A study was conducted to compare the growth performance and carcass characteristics of guinea fowl (GF) with Horro (HR) and Tilili (TL) local chickens, and Potchefstroom Koekoek (PK) exotic chicken. Seventy-five-day-old chicks from each genotype were used in 3 replications in a completely randomized design. Commercial starter and grower feed was fed ad libitum during the 20 weeks of the study. Daily dry matter intake in g/bird was greater for PK (70) than GF (63), HR (59), TL (61). The final body weight (FBW) g/bird was higher for PK (2022), intermediate for HR (1567) and TL (1539), and low for GF (1286). The average daily weight gain (ADG) was 9 g/bird for GF, 11 g/bird for HR and TL and 14 g/bird for PK. The eviscerated weight g/bird was highest for PK (1679), followed by HR (1323) and TL (1249) and lowest for GF (913). The breast weight (g/bird) was higher for PK (436) than GF (281), HR (311), and TL (284). The thigh weight was higher for PK (303) and HR (252), followed by TL (208) and lowest for GF (157). The abdominal fat content was higher for PK (29 g), followed by HR and TL (12 g each), and low for GF (6 g). The ultimate pH24 h of the breast was higher for GF (6.0) followed by PK (5.8), HR and TL (5.7). GF had higher pH24h thigh meat (6.2), others had 5.8. The meat from GF was darker than normal in color compared to chickens. The GF, HR and TL local chickens could be used as alternate meat-type poultry species with continuous selection.